Pengaruh Limbah Potongan Baja Ringan terhadap Kuat Lentur Beton - Sugik Firnanda; Dwi Kartikasari; Samsul Arif (Universitas Batanghari Jambi, 2026)
The utilization of concrete in the construction industry is highly massive due to its superior compressive strength; however, this activity also triggers a surge in waste, such as lightweight steel scraps. To address these environmental issues, this study examines the optimization of lightweight steel waste as a concrete additive because of its high tensile strength characteristics. Testing was conducted through an experimental method at the Civil Engineering Laboratory of Universitas Islam Lamongan to analyze the comparison of flexural strength between normal concrete and varied concrete mixtures. The percentages of the added material tested included 0%, 2%, 4%, and 6% of the total gravel weight. Based on the experimental results, normal concrete produced a flexural strength of 3.31 MPa, while the 2%, 4%, and 6% mixed variations sequentially surged to 5.16 MPa, 5.30 MPa, and 6.93 MPa. These data prove that an increase in the content of lightweight steel waste is directly proportional to the enhancement of the concrete's flexural strength quality. Therefore, this residual material is highly recommended as an alternative substitution ingredient to improve structural quality while reducing the negative impact of construction project waste.